2005
DOI: 10.2193/0091-7648(2005)33[1092:peorom]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of radiotransmitters on mourning doves

Abstract: It is critical to understand how radiotransmitters and their attachment techniques impact marked individuals. Many studies of transmitter effects assess only overt, deleterious effects. However, physiological effects caused by attachment techniques might compromise the integrity of resulting information. Our objectives, therefore, were to assess the efficacy of subcutaneous implants and determine the physiological effects on mourning doves (Zenaida macroura) using heterophil:lymphocyte (H:L) ratios, and fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Our results, although based on a small sample size, are consistent with studies that have revealed no changes in hematological parameters of captive doves with either backpack transmitters (Small et al 2004, 2005) or implanted transmitters (Schulz et al 1998, 2001, 2005). Such results support the continued use of transmitters, provided they meet suggested weight limits (<3% of body mass; Bird Banding Lab, Patuxent, Maryland).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results, although based on a small sample size, are consistent with studies that have revealed no changes in hematological parameters of captive doves with either backpack transmitters (Small et al 2004, 2005) or implanted transmitters (Schulz et al 1998, 2001, 2005). Such results support the continued use of transmitters, provided they meet suggested weight limits (<3% of body mass; Bird Banding Lab, Patuxent, Maryland).…”
Section: Discussionsupporting
confidence: 91%
“…The results of such studies indicate that transmitters may (Foster et al 1992, Mattson et al 2006) or may not (Hernandez et al 2004, Sunde 2006) have a negative impact on birds. More recently, investigators have examined possible adverse physiological effects of transmitters, such as increased stress levels (Schulz et al 2001, Small et al 2004, Schulz et al 2005, Small et al 2005) that could affect behavior, longevity, and reproduction, and have found little evidence of such effects. However, these studies were limited to birds in captivity and may not reflect conditions faced by wild birds, especially during potentially stressful parts of their life cycles.…”
mentioning
confidence: 99%
“…) and Mourning Doves (Schulz et al. ) were fitted with radio‐transmitters. For Dickcissels, levels were elevated 2 h after tag attachment, but declined to normal levels thereafter (Wells et al.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of between-group differences in FGM excretion suggests that AVED collars weighing 4% of individual body mass and worn 2 weeks do not induce a physiological stress response in captive white-tailed deer. Other FGM evaluations have shown no effects of attached transmitters on a variety of species, including African wild dogs (Lycaon pictus; Creel et al 1997), three-toed box turtles (Terrapene carolina; Rittenhouse et al 2005), and mourning doves (Zenaida macroura; Schulz et al 2005). Wells et al (2003) observed a spike in FGMs following attachment of transmitters in dickcissels (Spiza americana) that returned to baseline levels within 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…Stress hormone assessment is a useful tool for evaluating effects of animal-borne tags (e.g., Creel et al 1997, Wells et al 2003, Rittenhouse et al 2005, Schulz et al 2005 because it quantifies subtle changes in animal physiology (i.e., adrenal activity) rather than behavioral or demographic effects, which often only result after individual FGM levels remain high for sustained periods (Millspaugh and Washburn 2004). Previous FGM research has reported short-term effects from attached transmitters (,24 hr; Wells et al 2003), demonstrating the technique can detect acute stressors associated with attaching animal-borne tags.…”
mentioning
confidence: 99%